ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN PT. TBK SAMARINDA BERDASARKAN PSAK NO 34 ( REVISI 2015 ) - Wulandari, - Amelia (EKONOMIA, 2019)
Revenue and Expense Recognition Analysis of PT.TBK Samarinda Based on PSAK No. 34 (Revised 2015) period of February 2018 under the guidance of Robin Jhonatan and Ivana Nina Esterlin Barus.This writing aims to determine the recognition of income and expenses PT. TBK Samarinda are in compliance with PSAK No. 34 (Revision 2015) or not.The author put forward the hypothesis as follows: